MIEAP and ATG5 are tumor suppressors in a mouse model of BRAFV600E-positive thyroid cancer - Hamada, Koichiro; Kurashige, Tomomi; Shimamura, Mika; Arakawa, Hirofumi; Nakamura, Yasuyuki; Nagayama, Yuji (Frontiers in Endocrinology, 2022)
Mitochondria-eating protein (MIEAP) is a molecule important for non-canonical mitophagy and mitochondrial quality control. Our previous study has found that, together with increased mitochondrial biogenesis that compensates dysfunction of mitochondria, MIEAP plays a critical role in accumulation of mitochondria in thyroid oncocytic tumors that are composed of large polygonal cells with eosinophilic cytoplasm that is rich in abnormal mitochondria. To further study the significance of MIEAP in the pathogenesis of thyroid oncocytoma and extend our effort toward canonical mitophagy (a selective autophagy), we here conducted mouse studies using genetically engineered mice. BrafCA/wt mice developed thyroid cancers one year after intrathyroidal injection of adenovirus expressing Cre, while cancer development was observed at 6 months in adenovirus-Cre-injected BrafCA/wt;MieapKO/KO and BrafCA/wt;Atgflox/flox mice (where autophagy-related 5 (ATG5) is a component of autophagic machinery), although KO of either molecule alone was not sufficient for cancer development. These data demonstrate that MIEAP or ATG5 knockout (KO) accelerated thyroid cancer development, and clearly indicate that both MIEAP and ATG5 are tumor suppressors in thyroid carcinogenesis. However, cancers in adenovirus-Cre-injected BrafCA/wt;MieapKO/KO and BrafCA/wt;Atg5flox/flox mice were not oncocytic. In conclusion, we here show that MIEAP and ATG5 are both tumor suppressors in thyroid carcinogenesis, but as we have anticipated form the human data, KO of either molecule is not sufficient for a oncocytic phenotype in BRAFV600E-positive thyroid cancers. Combination of disruptive mitochondrial function and impaired mitochondrial quality control may be necessary to establish a mouse model of thyroid oncocytoma.